Thermal performance of a standing column well geothermal heat exchanger system using re-injection of bleeding water. (November 2019) - Lee, Changhee
Highlights: To investigate on the effective thermal conductivity compared with single well and two well geothermal heat exchange system. To measure the thermal performance in accordance with no bleeding and 20% bleeding water. To improve the performance of geothermal facilities equipped with an existing SCW geothermal heat exchanger, we aim to ensure operation stability of all geothermal facilities by switching to the process of balancing the well operation of the bleeding drainage. Abstract: A study on the change in thermal conductivity according to the bleeding rate of a standing column well (SCW)-type geothermal heat exchanger is experimentally performed in which the thermal conductivity of the geothermal heat exchanger is improved by approximately 165.4% at a bleeding rate of 10%. In studies conducted overseas, a numerical analysis was conducted, in which the effective thermal conductivity was improved by approximately 186.8% at a maximum bleeding rate of 30%. In this study, the change in the thermal conductivity was investigated when the bleeding water of a submerged heat-exchanger was re-injected into other adjacent SCW-type subsea heat exchangers using an artificial recharging method. The thermal conductivity in the two-well type SCW geothermal heat exchanger was 4.0 times higher than that of a single-well type SCW geothermal heat exchanger measured at the same bleeding rate. We consider that the two wells in the SCW geothermal heat exchangers are connected to each other by 90 and 280 m underground. Additionally, we consider that the bled discharge water in each geothermal heat exchanger is returned to the other underground heat-exchanger.